ABCB5 is activated by MITF and β‐catenin and is associated with melanoma differentiation - Louphrasitthiphol, Pakavarin; Chauhan, Jagat; Goding, Colin R. (Pigment cell and melanoma research, 2020)
Defining markers of different phenotypic states in melanoma is important for understanding disease progression, determining the response to therapy, and defining the molecular mechanisms underpinning phenotype‐switching driven by the changing intratumor microenvironment. The ABCB5 transporter is implicated in drug‐resistance and has been identified as a marker of melanoma‐initiating cells. Indeed ongoing studies are using ABCB5 to define stem cell populations. However, we show here that the ABCB5 is a direct target for the microphthalmia‐associated transcription factor MITF and its expression can be induced by β‐catenin, a key activator and co‐factor for MITF. Consequently, ABCB5 mRNA expression is primarily associated with melanoma cells exhibiting differentiation markers. The results suggest first that ABCB5 is unlikely to represent a marker of de‐differentiated melanoma stem cells, and second that ABCB5 may contribute to the non‐genetic drug‐resistance associated with highly differentiated melanoma cells. To reconcile the apparently conflicting observations in the field, we propose a model in which ABCB5 may mark a slow‐cycling differentiated population of melanoma cells.